Groups of Galaxies in the Nearby Universe: Proceedings of the ESO Workshop held at Santiago de Chile - Saviane, Ivo; Borissova, Jordanka; Ivanov, Valentin D. (Springer, 2007)
For every galaxy in the field or in clusters, there are about three galaxies in groups. The Milky Way itself resides in a group. Groups in the local universe offer the chance to study galaxies in environments characterized by strong interactions. In the cosmological context, groups trace large-scale structures better than clusters, the evolution of groups and clusters appears to be related. All these aspects of research are summarized in this book.
Includes bibliographical references and index
Keywords: Konferenzschrift -- 2005 -- Santiago de Chile; Galaxiengruppe